Pengembangan Media Pembelajaran Bahasa Indonesia Berbasis Website dengan Menggunakan Model ADDIE - Eden Putri Harefa; Desni Popintaria Waruwu; Apandi H. Hulu; Arozatulo Bawamenewi (Journal on Education, 2023)
This research was conducted to develop the abilities of high school students by using Website-based Indonesian language learning media with the ADDIE development model. The effective use of this learning media can increase active learning interactions. The purpose of this research is to increase student motivation in learning Indonesian. The results of this development research , it is recommended to be consistent and follow the instructions given. based on the results of the questionnaire trials distributed to students it reaches a rating of 4.6 with the "very decent" category.